Detection of antibodies against Trypanosoma cruzi in dogs from Costa Rica - Bonilla, Marta C. (2018)
Chagas disease is a zoonotic vector infection caused by Trypanosoma cruzi, and transmitted mainly by Triatoma dimidata in Costa Rica. The parasite infects humans, domestic and wild animals. Serological studies in dogs had been carried out in 12 of the 82 counties of Costa Rica, and dogs infected with T. cruzi were found in all the counties studied. The objective of the present research was to determine the seroprevalence of T. cruzi in dogs of 28 counties of Costa Rica and to establish if the seropositive dogs were presented in counties, where the vector or parasite had been previously reported in dogs, or if they were cases in other counties of the country not yet investigated. A total of 427 canine sera from 28 counties (23 not previously investigated) were analyzed by indirect hemagglutination (IHA) and indirect immunofluorescence assay (IFA). The seroprevalence determined in the 28 counties studied was 1.17 %. A total of 5 canines in 4 counties (Mora, San Rafael de Heredia, Liberia and Golfito) were positive. The presence of T. cruzi seropositive canines was established for the first time in 3 counties not reported before (Mora, Liberia and Golfito). More studies should be done in the counties with positive cases to determine the epidemiological characteristics that promote the appearance of T. cruzi infections. It is recommended to inform veterinarians about Chagas disease so they can consider it as a differential diagnosis in dogs, especially in counties where the presence of the agent has been reported, and to continue with systematic studies in communities and counties, to determine if the infection is distributed throughout the country.